The pull of Carabao Island: Investigating local tourists’ revisit intentions as basis for tourism and hospitality development - Turner Evon F. de Torres; Joanamae P. Juaneza; Krisha Klaire M. Vergara; Christine Gail S. Bacani; Joyce M. Fajiculay; Raymund Jashua F. Galang; Gesan P. Molina (School of Tourism, Universitas Ciputra Surabaya, 2026)
This quantitative study investigates factors influencing local tourists' revisit intentions to Carabao Island. Integrating the Theory of Planned Behavior with Customer Satisfaction and Loyalty frameworks, the research analyzed the interplay of perceived risk, satisfaction, and experience among 162 Filipino tourists. Findings identify Tourist Experience (Weighted Mean = 4.44) and Tourist Satisfaction (WM = 4.43) as the primary drivers for returning, both receiving